Dynamics and Challenges of the Zoning-Based Student Admission: A Study on Student Opportunities Across Regions - Chaniago, Syahril; Cahya Dewi , Desti; Hasanah, Siti; Yusanti, Yuniar; Mansur, Hamsi; Faqri, Rui (Indonesian Journal of Instructional Media and Model, 2024)
This article explores the dynamics of the zoning system in new student admissions (PPDB), analyzing the challenges faced and its impacts on educational opportunities for students in various regions. The PPDB zoning system aims to ensure a more equitable distribution of students based on their geographical location, as well as to reduce disparities in access to education. This study examines the challenges in implementing the zoning system, including public resistance, disparities in school quality, and logistical issues. Findings indicate that although the zoning system has the potential to improve educational accessibility, its implementation often encounters obstacles that may hinder its objectives. Additionally, this article evaluates the impact of the zoning system on students' educational opportunities. The analysis shows that the zoning system can enhance educational access for students from diverse socio-economic backgrounds. However, disparities in educational quality across regions remain a significant issue, affecting the effectiveness of the system in creating equal educational opportunities. In conclusion, this article suggests the need for policy adjustments and implementation strategies to address existing challenges and maximize the positive impacts of the PPDB zoning system. This is expected to create more equitable and high-quality educational access across all regions. This study provides valuable insights for policymakers and education practitioners in developing a more effective and fair zoning system, contributing to the improvement of educational quality in Indonesia.